Absorbance changes accompanying the fast fluorescence induction in the purple bacterium Rhodobacter sphaeroides - Bína, David; Litvín, Radek; Vácha, František (Photosynthesis research, 2010)
The authors present a study of the fluorescence and absorbance transients occurring in whole cells of purple nonsulfur bacterium Rhodobacter sphaeroides on the millisecond timescale under pulsed actinic illumination. The fluorescence induction curve is interpreted in terms of combination of effects of redox changes in the reaction center and the membrane potential. The results of this study support the view that the membrane potential act predominantly to increase the fluorescence yield. Advantages of the pulsed actinic illumination for study of the operation of the electron transport chain in vivo are discussed.
Keywords: membránové potenciály; Absorption; karotenoidy; absorpce; kinetika; Rhodobacter sphaeroides; Light; Spectrometry, Fluorescence; Membrane Potentials; Carotenoids; Oxidation-Reduction; světlo; fluorescenční spektrometrie; oxidace-redukce; Kinetics